2019
DOI: 10.1186/s40170-018-0193-4
|View full text |Cite
|
Sign up to set email alerts
|

The novel function of tumor protein D54 in regulating pyruvate dehydrogenase and metformin cytotoxicity in breast cancer

Abstract: BackgroundThe role of tumor protein D54 in breast cancer has not been studied and its function in breast cancer remains unclear. In our previous pharmacogenomic studies using lymphoblastoid cell line (LCL), this protein has been identified to affect metformin response. Although metformin has been widely studied as a prophylactic and chemotherapeutic drug, there is still a lack of biomarkers predicting the response to metformin in breast cancer. In this study, we revealed the novel function of TPD54 in breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In this experiment, the level of formate was decreased in the high-fat diet. These results were the same as those of previous studies, which also showed that the formate level was significantly decreased in the obese group compared to the healthy control group [ 32 ]. Inosine, an endogenous metabolic derivative of adenosine, decreased in the high-fat diet group and increased in the positive control group and the A. sessiliflorus fruit administration group.…”
Section: Discussionsupporting
confidence: 91%
“…In this experiment, the level of formate was decreased in the high-fat diet. These results were the same as those of previous studies, which also showed that the formate level was significantly decreased in the obese group compared to the healthy control group [ 32 ]. Inosine, an endogenous metabolic derivative of adenosine, decreased in the high-fat diet group and increased in the positive control group and the A. sessiliflorus fruit administration group.…”
Section: Discussionsupporting
confidence: 91%
“…Tumor protein D54 (TPD54) is another protein that we found to be greatly increased after weight loss. Recently its mitochondrial location has been demonstrated, and it has been hypothesized that TPD54 knockdown decreases pyruvate dehydrogenase enzyme activity, reducing mitochondrial oxidative phosphorylation [64].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their mechanism of action—improvement in hyperglycemia, insulin sensitivity, decreased body weight—there were also expectations for their beneficial effect on cancer risk. In vitro and animal studies show their significant potential for protection against cancer formation and progression [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. However, randomized and observational studies, and their meta-analyzes, did not confirm these hopes [ 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was abrogated by insulin infusion. Thus, in case of obesity-related cancers canagliflosin exerts its oncoprotective effect through insulin- and glucose-lowering action [ 134 ]. In a study by Shiba et al canagliflozin attenuated development of HCC in a mouse model of human NASH.…”
Section: Antidiabetic Medications and Cancermentioning
confidence: 99%